2022
DOI: 10.1038/s41598-022-12538-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of CO2 uptake in CO2 hydrates formation with amino acids as kinetic promoters and its dissociation at high temperature

Abstract: The dissociation of CO2 gas hydrates (GH) with amino acid kinetic promoters and without promoters was studied at a high temperature of 90 °C for a period of 20 min to understand the percentage of CO2 gas and to select the best promoter that aids CO2 gas entrapment along with stability at a high temperature. The possibility of using four hydrophobic food grade amino acids, namely cysteine, valine, leucine, and methionine, and one surfactant, lecithin, as kinetic promoters for CO2 GH has been studied. The amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The CO 2 GH was created in a reactor installed at the Department of Process Analytics and Cereal Science, University of Hohenheim, Stuttgart, Germany, in conjunction with installation help from the Institute of Fluid Mechanics (LSTME), FAU Erlangen, Germany [ 3 , 21 , 22 ]. The CO 2 GH was created by pouring 500 mL of distilled water mixed with natural amino acids as promoters into the reactor vessel, which was connected to the CO 2 gas cylinder at a pressure of 37 bars and a temperature of 273.15 K. After the gas molecules have been dissolved at a low temperature, the GH synthesis begins with nucleation and lasts three hours [ 3 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO 2 GH was created in a reactor installed at the Department of Process Analytics and Cereal Science, University of Hohenheim, Stuttgart, Germany, in conjunction with installation help from the Institute of Fluid Mechanics (LSTME), FAU Erlangen, Germany [ 3 , 21 , 22 ]. The CO 2 GH was created by pouring 500 mL of distilled water mixed with natural amino acids as promoters into the reactor vessel, which was connected to the CO 2 gas cylinder at a pressure of 37 bars and a temperature of 273.15 K. After the gas molecules have been dissolved at a low temperature, the GH synthesis begins with nucleation and lasts three hours [ 3 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…To stabilize the structure, suitable sized guest molecules are caged in hydrogen-bonded water molecules without any chemical interactions. The most prevalent GH guest molecules are ethane, nitrogen, and carbon dioxide [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 GH was produced in a reactor installed at the Department of Process Analytics and Cereal Science, University of Hohenheim, Stuttgart, Germany, in collaboration with installation assistance from the Institute of Fluid Mechanics (LSTME), FAU Erlangen-Nuremberg, Erlangen, Germany [ 32 ]. The CO 2 GH was produced by the addition of 500 mL of distilled water into the reactor vessel connected to the CO 2 gas cylinder with an optimum pressure of 32 bars and a lower temperature of 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 GH was produced by the addition of 500 mL of distilled water into the reactor vessel connected to the CO 2 gas cylinder with an optimum pressure of 32 bars and a lower temperature of 1 °C. The CO 2 GH was produced after a period of 4 h [ 32 ], and was stored at −20 °C until further used for the bread baking process.…”
Section: Methodsmentioning
confidence: 99%
“…Because they are natural molecules, which do not pollute the environment, amino acids have recently attracted the attention of researchers. Srivastava et al 152 observed that the combination of lecithin (a surfactant) and hydrophobic amino acids improved the formation characteristics, including the induction time and formation rate, of the carbon dioxide hydrate. As shown in Figure 8a, the combination comprising leucine, methionine, and lecithin exhibited the highest gas consumption.…”
Section: Surfactants + Amino Acidsmentioning
confidence: 99%